HUBUNGAN SIKAP DAN NORMA SUBJEKTIF TENTANG PROMOSI DIRI TERHADAP MINAT MELAKUKAN PROMOSI DIRI DALAM MENCARI PEKERJAAN DI MEDIA SOSIAL - Putri Dwikurnia, Josephine; Manalu, S. Rouli; Luqman, Yanuar (Interaksi Online, 2024)
The intense job competition in Indonesia has made it difficult for job seekers in Indonesia to find a job. Self-promotion could help people to find job easily. The study analyzed whether there was a relationship between the attitude about self-promotion and the subjective norm of self promotion toward the individual's intention in doing self-promoting on social media to find a job. The hypothesis is based on the Theory of Reasoned Action. The sampling of this study was done using non-probability samplings, specifically purposive samplers. The study took 300 respondents. The sample criteria for the study are individuals aged 15-24 years who are jobseeker. This consideration was due to the highest unemployment rate at the age range of 20-24 years, followed by the 15-19 year range. The hypothesis was tested using Kendall's W analysis with SPSS 29. Online questionnaire shared through Instagram, Tiktok, Facebook, Linkedin, and WhatsApp. The results of the research showed that the attitude and the subjective norms of have a relationship with the interest in doing self promotion on social media to find a job with a significance of 0,001<0,05 which means very significant. For the W value of 0,077 or 7,7% which means the relationship between the attitudes and the subjective norm towards the intention of doing self-promoting on social networks for finding a job is very weak. The findings of this study are in line with the theory used